World healthcare cooperatives : challenges and opportunities - Tripathy, K. K.; Kumari, Sneha; Venkatesh, V. G.; Jayalakshmi, R.; Nair, M. P. Sukumaran (Emerald Publishing Limited, 2023)
The healthcare industry is one of the largest and fastest-growing service industries in the world. The respective merits of public and private healthcare systems are continually debated, but a third system - that of healthcare cooperatives - is rapidly emerging as a universal, community-focused and cost-effective alternative. Rooted in remarkable examples from every corner of the world, World Healthcare Cooperatives highlights both the challenges a successful healthcare cooperative may face, as well as its proven effectiveness in making a difference. Understanding that, for many, especially in developing countries, private hospitals and healthcare insurance plans are expensive and out of reach, and that globally many public healthcare systems are under-resourced, chapters demonstrate how healthcare cooperatives have a critical role to play in providing services sustainably and at an affordable cost. Addressing the persistent gap between supply and demand in the healthcare sector, the authors highlight the capability of healthcare cooperatives to create a positive impact. With examples from Canada, Argentina, Japan, Africa, Brazil, Columbia, Sri Lanka, Spain, and India, chapters showcase the services that cooperatives can offer their communities, including the establishment of hospitals, medical facilities, and other infrastructure, as well as opportunities in biotechnology and information technology research. Considering more than 100 million households worldwide that have benefitted from healthcare cooperatives, this pioneering collection triggers a new direction of research to support those seeking to establish healthcare infrastructure in developing and least developed countries in achieving universal healthcare for all.